2012
DOI: 10.1002/smj.2035
|View full text |Cite
|
Sign up to set email alerts
|

Performance effects of top management team demographic faultlines in the process of product diversification

Abstract: Expanding into new product areas is an important part of the growth strategy of many firms, but there is still more to learn about how it affects firm performance. We believe that as the top management team (TMT) is responsible for coordinating product expansion, looking there can yield valuable clues. We argue that diversification entails significant additional information processing and that this strains top managerial resources. We hypothesize that task‐related faultlines within the TMT may help it cope wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
151
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(155 citation statements)
references
References 176 publications
(269 reference statements)
2
151
0
2
Order By: Relevance
“…They found that task conflict was more positively related to firm performance in TMTs (as compared with other groups). Hutzschenreuter & Horstkotte (2013) examined demographic fault lines within 61 TMTs of German firms. They found that demographic fault lines were negatively related to product diversification.…”
Section: Teams and Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that task conflict was more positively related to firm performance in TMTs (as compared with other groups). Hutzschenreuter & Horstkotte (2013) examined demographic fault lines within 61 TMTs of German firms. They found that demographic fault lines were negatively related to product diversification.…”
Section: Teams and Groupsmentioning
confidence: 99%
“…Such research uses firms within or across different countries and is helpful in establishing the generalizability of the strategic value of OP/OB. Examples of cross-cultural research in recruitment (Han & Han 2009, Martins & Lima 2006), leadership (de Luque et al 2008, training (Garcia 2005), and TMTs (Hutzschenreuter & Horstkotte 2013) are discussed above. However, this research does not fully integrate cross-cultural dynamics into the study of OP/OB as a source of international competitive advantage.…”
Section: Cross-cultural Issuesmentioning
confidence: 99%
“…Hutschenreuter & Horstkotte 2013). When singling out one dimension along which to study diversity, effects that results in other dimensions of board diversity not being included in a study may unduly be ascribed to the single dimension of board diversity actually included (Hutzschenreuter & Horstkotte 2013). In addition, various dimensions of board diversity can interact to have effects on firm performance that differ markedly from their main effects.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, the strength of BDF is at a stage of too high or too low. As BDF is closely related to the relationship conflict and process conflict, too high or too low strength of BDF may cause the relationship conflict and process conflict among team members (Hutzschenreuter and Horstkotte, 2013) [3]. It also hinders TMT members to objectively deal with and evaluate the team internal information and harms the full integration and utilization of TMT members' internal resources and abilities (Jehn, 1995) [40], leading to the sub optimal diversification strategy.…”
Section: Discussionmentioning
confidence: 99%
“…The concept has investigated the effect of multiple demographic characteristics within team members on team performance, strategic decision and corporate performance (Knippenberg et al, 2011) [20]. Meanwhile, Hutzschenreuter and Horstkotte (2013) divided TMT faultlines into task-related faultlines and bio-demographic faultlines, and pointed out its influence on corporate expansion strategy [3]. Thus, this study adopts the TMT faultlines to stand for the changes of TMT characteristic, which is more accurate to reflect the moderate effect of TMT on the diversification strategy decision-making and makes the study be more scientific and precise.…”
Section: Literature Reviewmentioning
confidence: 99%